TAK-925, an orexin 2 receptor-selective agonist, shows robust wake-promoting effects in mice - Yukitake, Hiroshi; Fujimoto, Tatsuhiko; Ishikawa, Takashi; Suzuki, Atsushi; Shimizu, Yuji; Rikimaru, Kentaro; Ito, Mitsuhiro; Suzuki, Motohisa; Kimura, Haruhide (Pharmacology, biochemistry and behavior, 2019)
Orexin-producing neurons in the lateral hypothalamus are a critical regulator of sleep/wake states, and their loss is associated with narcolepsy type 1 (NT1). Orexin peptides act on two G protein-coupled receptors: orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R). OX2R knockout (KO) mice, but not OX1R KO mice, showed clear narcolepsy-like phenotypes, including fragmented sleep-wake cycles. Moreover, OX2R-selective antagonists have been shown to induce sleepiness in mice, and activation of OX2R has been reported to increase wakefulness. In this study, we characterized in vitro and in vivo profiles of a novel, highly selective OX2R agonist, TAK-925 [methyl (2R,3S)-3-[(methylsulfonyl)amino]-2-{[(cis-4-phenylcyclohexyl)oxy]methyl}piperidine-1-carboxylate]. TAK-925 activated human recombinant OX2R with 50% effective concentration value of 5.5 nM, and showed >5,000-fold selectivity over OX1R in calcium mobilization assays. TAK-925 induced OX2R-downstream signals similar to those displayed by orexin peptides in Chinese hamster ovary cells stably expressing human OX2R. In an electrophysiological study, TAK-925 activated physiological OX2R on histaminergic neurons in the mouse tuberomammillary nucleus (TMN). Subcutaneous (SC) administration of TAK-925 also modulated neuronal activity in various brain regions, including TMN, as measured by an immunohistochemical analysis using an anti-c-fos antibody. TAK-925 (SC) increased wakefulness in wild-type mice, but not in OX2R KO mice, during their sleep phase, demonstrating that a highly selective OX2R agonist can increase wakefulness in mice via OX2R activation. TAK-925 may have therapeutic potential to reduce hypersomnia in multiple disorders including NT1. •TAK-925 is a highly potent and selective OX2R agonist.•Activation pattern of OX2R downstream signals by TAK-925 is similar to those induced by orexin peptide.•TAK-925 promotes neuronal activities of histaminergic neurons in the mouse TMN.•TAK-925 shows robust wake-promoting effects in wild-type mice, but not in OX2R KO mice.